Complete genome of a nonphotosynthetic cyanobacterium in a diatom reveals recent adaptations to an intracellular lifestyle - Nakayama, Takuro (National Academy of Sciences, 2014)
The evolution of mitochondria and plastids from bacterial endosymbionts were key events in the origin and diversification of eukaryotic cells. Although the ancient nature of these organelles makes it difficult to understand the earliest events that led to their establishment, the study of eukaryotic cells with recently evolved obligate endosymbiotic bacteria has the potential to provide important insight into the transformation of endosymbionts into organelles. Diatoms belonging to the family Rhopalodiaceae and their endosymbionts of cyanobacterial origin (i.e., “spheroid bodies”) are emerging as a useful model system in this regard. The spheroid bodies, which appear to enable rhopalodiacean diatoms to use gaseous nitrogen, became established after the divergence of extant diatom families. Here we report what is, to our knowledge, the first complete genome sequence of a spheroid body, that of the rhopalodiacean diatom Epithemia turgida. The E. turgida spheroid body (EtSB) genome was found to possess a gene set for nitrogen fixation, as anticipated, but is reduced in size and gene repertoire compared with the genomes of their closest known free-living relatives. The presence of numerous pseudogenes in the EtSB genome suggests that genome reduction is ongoing. Most strikingly, our genomic data convincingly show that the EtSB has lost photosynthetic ability and is metabolically dependent on its host cell, unprecedented characteristics among cyanobacteria, and cyanobacterial symbionts. The diatom–spheroid body endosymbiosis is thus a unique system for investigating the processes underlying the integration of a bacterial endosymbiont into eukaryotic cells.